Antibiotic resistance and biofilm-forming ability of α-toxin-positive Clostridium septicum isolates worsen patient prognosis - Kuzma, Jozef; Zavala-Meneses, Sofía Guadalupe; Skultety, Ludovit; Chmelar, Dittmar; Ficik, Jozef; Palcová, Lenka (APMIS. Acta pathologica, microbiologica et immunologica Scandinavica, 2023)
A total of, 78 Clostridium septicum (CLSE) isolates were screened for genes encoding: α-toxin, flagellin, and resistance to vancomycin (VANg). The isolates were also tested for their ability to form biofilm and their antibiotic susceptibility. All isolates were positive for α-toxin and flagellin genes. However, only 19 isolates (24.3%) showed prevalence for VANg. We observed the strongest capacity to form a biofilm (100%) in isolates from patients with oncologic or septic and febrile diagnoses. This percentage was also very high in patients with colitis and gastrointestinal hemorrhage (72.7%). No less than 43 isolates showed antibiotic resistance, and 21 were multidrug-resistant (MDR). Interestingly, our studies showed a correlation between antibiotic resistance and biofilm formation. A statistically significant difference was observed between biofilm-forming MDR isolates and those with low/no biofilm-forming ability. However, the most impressive observation was the correlation with mortality rate. While the overall mortality rate for CLSE infections was 16.7% (13/78), the mortality rate for patients infected with MDR isolates forming biofilm moderately or strongly reached 38.1% (8/21). This number increased even further when only infections with the biofilm-forming VANg-positive isolates were considered (61.5%; 8/13). Therefore, the ability of a VANg-positive CLSE isolate to form a biofilm has been suggested as a biomarker of poor prognosis.
Keywords: vankomycin; prognóza; Prognosis; Drug Resistance, Multiple, Bacterial; Clostridium septicum; Flagellin; lidé; biofilmy; antibakteriální látky; Anti-Bacterial Agents; Biofilms; mnohočetná bakteriální léková rezistence; flagelin; Vancomycin; Humans